2023
DOI: 10.1111/1365-2745.14071
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fixation responds to soil nitrogen at low but not high light in two invasive understory species

Abstract: Light and soil nitrogen availability can be strong controls of plant nitrogen (N) fixation, but data on how understory N‐fixing plants respond to these drivers are limited despite their important role in ecosystem N cycling. Furthermore, ecosystem N cycling can be altered by the introduction of species with nutrient use patterns that differ from natives. We assessed how N fixation of two exotic, understory species responded to varying light and soil N environments. We sampled leaf tissue from Mimosa pudica L.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 85 publications
1
2
0
Order By: Relevance
“…The light interpretation is also consistent with another study in our experimental plots in Waiakea. Mimosa pudica and Desmodium triflorum, two ground-layer legume species that recruited naturally under and near our Gliricidia, Casuarina, and Psidium trees, had %N dfa values similar to those of our trees (averages of 58%-82%), but their %N dfa in the fertilized plots decreased with shade (Schmidt et al, 2023).…”
Section: Why Obligate Snf or Incomplete Downregulation And Evidence F...supporting
confidence: 53%
“…The light interpretation is also consistent with another study in our experimental plots in Waiakea. Mimosa pudica and Desmodium triflorum, two ground-layer legume species that recruited naturally under and near our Gliricidia, Casuarina, and Psidium trees, had %N dfa values similar to those of our trees (averages of 58%-82%), but their %N dfa in the fertilized plots decreased with shade (Schmidt et al, 2023).…”
Section: Why Obligate Snf or Incomplete Downregulation And Evidence F...supporting
confidence: 53%
“…However, Funk et al (2013) also observed that N fixers tended to have a greater proportion of leaf N associated with photosynthesis than non‐fixers. This may be due to N fixers specializing in high‐light environments (McCulloch & Porder, 2021; Schmidt et al, 2023; Taylor & Menge, 2018; and therefore having lower shade tolerance than non‐fixers; Menge et al, 2010), where N associated with photosynthesis is likely to be more beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…The control treatment received 0.1 g N m −2 y −1 as ammonium nitrate in years 2 and 3 and none in all other years. This small addition of ammonium nitrate was isotopically labeled in order to facilitate the measurement of symbiotic N fixation, which was a major goal of the overall experiment [ 63 ], though not our focus here. As is standard in the enriched isotopic pool dilution method of measuring symbiotic N fixation [ 64 ], we needed to add a small amount (0.1 g N m −2 y −1 ) of labeled N to measure N fixation.…”
Section: Methodsmentioning
confidence: 99%